Public Execution Sale According to Provisions of Civil Procedure Legislation from 1865 - Kulauzov, Maša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The article sheds light on provisions of Code of Civil Procedure from 1865 concerning public execution sale as the last stage in process of execution of court decisions. Public auction of debtor′s movable and immovable property held by police authorities is conducted in order to satisfy unpaid creditor′s obligations which debtor did not want to discharge free willingly. Given the delicacy and sensitivity of public sale that can cause serious disturbances for execution debtors, provisions regarding execution sale had been very carefully drafted after thorough and detailed discussion between the author of the draft and the State Council′s Commission. Aforementioned discussion was meticulously scrutinized in this paper. Analysis of original provisions of Code from 1865 along with all its amendments and supplements undoubtedly showed that debtor, as the weaker party, enjoyed special protection under law. Firstly, he had the right to select and indicate to the authorized official the property which was to be sold at public auction. If some irregularities occured in the conduct of the execution sale, debtor was entitled to address to court and request its nullification. Minister of internal affairs Jovan Đaja in his draft from 1891 even suggested that debtor should be allowed to pay his debt in every moment until the public sale has ended. Beside bettering debtor′s position, Code amendments, as well as the drafts from 1872 and 1891 that never came into effect, proposed various measures in order to make execution process more effective and faster. These measures were also examined in this article.